Role of Recombinant Human Erythropoietin in Neonates with Moderate to Severe Hypoxic Ischemic Encephalopathy - A Prospective Cohort Study - Nagaraju, C.S.; Naganoor, Ravindra; Charki, Siddu; Patil, M.M. (International Journal of Child Health and Nutrition, 2025)
Background: Hypoxic-ischemic encephalopathy (HIE) is a significant brain injury that occurs when there is inadequate oxygen supply to the brain during the neonatal period. Newer researches have established that rhEPO, human recombinant erythropoietin possesses neurological, neuro-restorative, and anti-inflammatory properties in asphyxia newborns. These effects are invaluable in enhancing outcomes for neonates diagnosed with hypoxic-ischemic encephalopathy-HIE Aims: To evaluate the role and effects of human recombinant erythropoietin in moderate to severe hypoxic-ischemic encephalopathy in neonates. Objective: To assess the safety and feasibility of rhEPO in asphyxiated neonates with moderate to severe encephalopathy. To know and to correlate the effect of EPO on EEG, RI (resistive index) in Neurosonogram (NSG), MRI brain in asphyxiated neonates with moderate to severe encephalopathy. Materials and methods: This is a Prospective Cohort Study conducted over 12-18 months with a sample size of 92, comprising 46 participants in each group. All neonates received intravenous recombinant human erythropoietin (rhEPO) after 6 hours of life. A total of 5 doses were administered. Results: In the EPO group, 47.8% (n = 22) had moderate encephalopathy, while 52.2% (n = 24) had severe encephalopathy. In our study we found that Amplitude–integrated electroencephalogram [aEEG] showed burst suppression [21.7% vs. 6.5%], low voltage [10.9% vs. 4.3%], flat trace [13.0% vs. 8.7%], and status epilepticus [6.5% vs. 2.2%] in the control group in comparison with EPO Group. A neurosonogram [NSG] was done and showed Abnormal RI [56.5% vs. 15.2%] and Normal RI [43.5% vs. 84.8%] in the control group in comparison with the EPO Group. Brain magnetic-resonance imaging [MRI] done at discharge showed severe brain injury [32.6% vs. 8.6%] and regional-specific HIE [19.5% vs. 39.1%] in the control group in comparison with the EPO Group. Mortality outcome was 10.8% in control group in comparison with EPO Group(2.17%). Conclusion: The study concludes that administering recombinant human erythropoietin (rhEPO) to newborns with moderate to severe hypoxic-ischemic encephalopathy (HIE) is safe and practical. In comparison to the control group, rhEPO treatment significantly reduces the occurrence of an abnormal resistive index (RI). Furthermore, EPO-treated neonates showed improvements in electroencephalographic (EEG) patterns, neurosonogram (NSG) resistive index, and MRI brain findings, suggesting possible neuroprotective advantages.